Clinical impact of osteosarcopenia on mortality, physical function and chronic inflammation: a 9-year follow up cohort study.: Osteosarcopenia, mortality and physical function - sepulveda loyola, Walter; de Barros Morselli, Jaqueline; Araya-Quintanilla, Felipe; Teixeira, Denilson; Alvarez-Bustos, Alejandro; Molari, Mario; Valenzuela- Fuenzalida, Juan José; Probst, Vanessa Suziane (Nutrición Clínica y Dietética Hospitalaria, 2023)
Objective: This study aimed to determine the impact of osteosarcopenia on important clinical and functional outcomes in older adults. Methods: 242 community-dwelling older adults from the study on ageing and longevity (ELLO data from 2009 to 2018). Subjects underwent body composition analysis by dual energy X-ray absorptiometry and bioelectrical impedance, and assessments for aerobic capacity and muscle strength including the incremental shuttle walking test (ISWT), 6-minutes walking test (6MWT), handgrip strength (HGS) and sit-to stand test (STS). Static balance was assessed by one-legged stance test (OLST) and chronic inflammation by IL-6 and tumor necrosis factor alpha (TNF-α). Osteosarcopenia was defined as low bone mineral density (BMD) (T-score<-1) combined with low phase angle (PhA). Comparisons were run with Students T test and Man-Whitney test. Survival probabilities were estimated using the Kaplan-Meier method. Receiver operating characteristic curve was used to analyze the association of PhA with mortality and to find the best cut-point. Results: The proportion of individuals who died in a 9-year follow up was higher in individuals with Osteosarcopenia (25%) compared to without osteosarcopenia (9%) (p=0.015). Osteosarcopenia was associated with mortality (HR: 1.4; 95% CI 1.02 - 1.29; p = 0.0151). Subjects with osteosarcopenia compared to without it presented worse performance in the ISWT (514 ±19 m vs. 621 ± 16 m), 6MWT (515 ± 7 m vs. 538 ± 6 m, p< 0.05), OLST (13.5 ±10.2 s vs.16.7 ±8.3 s) and HGS (25 ± 7 Kg vs. 28 ± 9 K5); p< 0.05 for all. The cut point used to PhA was ≤ 6.07º for both male and female (AUC: 0.687; Sensibility: 64% and Specificity: 61% for mortality). Conclusion: Osteosarcopenia diagnosed with low phase angle combined with low BMD is highly associated with mortality. Additionally, older adults with osteosarcopenia presented worse aerobic capacity, balance and muscle strength.